1992
DOI: 10.1111/j.1365-2044.1992.tb03143.x
|View full text |Cite
|
Sign up to set email alerts
|

Six months of shivering in a district general hospital

Abstract: SummaryOf 2595 patients admitted to a recovery room in Derbyshire Royal Infirmary over a 6-month period, 164 (6.3%) shivered postoperatively. Data regarding the anaesthetic techniques to which these patients had been subjected were gathered from the Derby Anaesthetic Audit System. Subsequent analysis demonstrated the importance of a number of factors that led to shivering, including male gender, anaesthetic techniques involving spontaneous ventilation. and anticholinergic premedication. The administration of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
2
8

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 13 publications
6
40
2
8
Order By: Relevance
“…Consequently oxygen consumption may increase by up to 500%, with a concomitant increase in carbon dioxide production [I]. It has been shown to be more common with decreasing age in adults [2], but its true incidence is uncertain. Moir and Doyle found that between 17 and 32% of children shivered following halothane anaesthesia [3].…”
mentioning
confidence: 99%
“…Consequently oxygen consumption may increase by up to 500%, with a concomitant increase in carbon dioxide production [I]. It has been shown to be more common with decreasing age in adults [2], but its true incidence is uncertain. Moir and Doyle found that between 17 and 32% of children shivered following halothane anaesthesia [3].…”
mentioning
confidence: 99%
“…Anticholinergic premedication increases the incidence of postanaesthetic shivering, by a peripheral mechanism that is postulated to involve alteration in skin blood flow [8]. A similar line of reasoning could lead one to suggest other possible mechanisms of action which could include serotonergic effects since ketanserin reduces postanaesthetic shivering [9] or an effect on peripheral vasodilatation. The latter is mimicked by clonidine which also reduces shivering postoperatively [9].…”
Section: The Treatment Of Postoperative Shiveringmentioning
confidence: 99%
“…A similar line of reasoning could lead one to suggest other possible mechanisms of action which could include serotonergic effects since ketanserin reduces postanaesthetic shivering [9] or an effect on peripheral vasodilatation. The latter is mimicked by clonidine which also reduces shivering postoperatively [9].…”
Section: The Treatment Of Postoperative Shiveringmentioning
confidence: 99%
See 2 more Smart Citations